Characteristic Properties of CEB Made of Gypsum Soil - Humam Th. Al-Jumaili, Osamah I. Mahmood, Ali A. Habeeb (International Journal of Advanced Science and Technology, 2019)
Compressed Earth Blocks (CEB) are produced utilizing stabilizing materials to obtain suitable endurance and strength to make proper construction material. Those blocks would be an excellent option for cities and rural areas where gypsum soil is available in abundance. This research paper includes an experimental investigation to find the ability to produce CEB from locally available gypsum soil by using chemical and physical. The effect of using cement as a chemical stabilizer at different cement to soil content with various water mixing content on CEB physical and mechanical properties including compressive strength, water absorption, dry shrinkage, and elasticity was studied. The properties of the blocks were carefully examined.    The study showed adding ordinary Portland cement to gypsum soil to produce CEB affected its properties by significant increasing. The compressive strength by 30.3% and reducing water absorption by 5.6. Moreover, the dry shrinkage of the blocks was decreased by 35 %, and the highest rate of shrinking was recorded in the first 3 days and stopped at 14 days. Finally, CEB showed a significant improvement in elasticity when increasing the cement content in the mix.Keywords: Low-Cost Construction, Compressed Earth blocks, Gypsum soil, Chemical Stabilization, Compressive Strength